2022
DOI: 10.1039/d2qm00789d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of rigidity- and planarity-promoted, state-dependent doping of conjugated ladder-type molecules

Abstract: Determining the doping mechanism of organic semiconductors (OSCs) by neutral dopants, whether through the formation of ion-pair (IP) or charge transfer complex (CTC), remains an open challenge. It is hypothesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Interestingly, contrary to the precursor polymer, cLP 2 was found to be readily doped with F 4 TCNQ. It was recently reported that the extended π‐conjugation and coplanar nature of the ladder‐type molecules are crucial to facilitate charge transfer interactions with F 4 TCNQ [15] …”
Section: Review/discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, contrary to the precursor polymer, cLP 2 was found to be readily doped with F 4 TCNQ. It was recently reported that the extended π‐conjugation and coplanar nature of the ladder‐type molecules are crucial to facilitate charge transfer interactions with F 4 TCNQ [15] …”
Section: Review/discussionmentioning
confidence: 99%
“…It was recently reported that the extended π-conjugation and coplanar nature of the ladder-type molecules are crucial to facilitate charge transfer interactions with F 4 TCNQ. [15] Ring-closing olefin metathesis was also utilized for the synthesis of a porous ladder polymer network (PLAN), which led to entropically favorable gas adsorption. [16] Despite the successful examples of cLP synthesis via RCM, using vinyl functional which are rather challenging to introduce and have moderate functional group tolerance during the reactions, might confine the synthetic approach utilizing RCM.…”
Section: Ring-closing Olefin Metathesismentioning
confidence: 99%